2017
DOI: 10.1002/2016jg003734
|View full text |Cite
|
Sign up to set email alerts
|

Gas transfer velocities in small forested ponds

Abstract: Inland waters actively exchange gases with the atmosphere, and the gas exchange rate informs system biogeochemistry, ecology, and global carbon budgets. Gas exchange in medium‐ to large‐sized lakes is largely regulated by wind; yet less is known about processes regulating gas transfer in small ponds where wind speeds are low. In this study, we determined the gas transfer velocity, k600, in four small (<250 m2) ponds by using a propane (C3H8) gas injection. When estimated across 12 h periods, the average k600 r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
27
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(32 citation statements)
references
References 52 publications
4
27
1
Order By: Relevance
“…Diel variations in the stability of the atmosphere and within ponds and lakes will contribute to between site differences. For example, 12 h k 600 from ponds in temperate regions tend to be lower than we compute (Holgerson et al ). For winds of ∼ 2 m s −1 , Clark et al () obtained average values ranging from 0.5 cm h −1 to 3 cm h −1 at a larger pond.…”
Section: Discussioncontrasting
confidence: 55%
“…Diel variations in the stability of the atmosphere and within ponds and lakes will contribute to between site differences. For example, 12 h k 600 from ponds in temperate regions tend to be lower than we compute (Holgerson et al ). For winds of ∼ 2 m s −1 , Clark et al () obtained average values ranging from 0.5 cm h −1 to 3 cm h −1 at a larger pond.…”
Section: Discussioncontrasting
confidence: 55%
“…3, d) within the range of previously published values (Torgersen and Branco, 2008;Holgerson et al, 2017; and similar to values found in the same system using ordinary floating chambers (not shown). Because 25 the ventilation of the chamber headspace occurs through dilution with atmospheric air, CO 2 concentrations do not always reach the ambient atmospheric values (Fig.…”
Section: Discussionsupporting
confidence: 77%
“…Total annual N 2 O flux from Finnish lakes (total LA 32,663 km 2 ) was estimated as 0.6–0.8 Gg N 2 O‐N/year, based on the areas of the lake size distribution by Raatikainen and Kuusisto () and the evasion estimates for the different lake size classes (Figure ). Both Holgerson et al () and Heiskanen et al () approaches resulted in an estimate of 0.6 Gg N 2 O‐N/year for Finnish lakes, when the median N 2 O evasion estimates of different lake size classes were multiplied with the respective lake surface area distribution. The Vachon and Prairie () approach resulted in a little bit larger estimate of 0.8 Gg N 2 O‐N/year (Table ; Tables S1 and S2).…”
Section: Resultsmentioning
confidence: 99%
“…where F gas is the lake-atmosphere flux of N 2 O, kN 2 O is the gas transfer velocity (m/day), C gas is the concentration of the gas in the surface water (μmol/L), C eq is the concentration of the gas (μmol/L) in equilibrium with the atmosphere. Since the data behind measured gas transfer coefficients (k values) are limited and the relationship between lake size and k values varies, we used three approaches to estimate lake-atmosphere gas exchange (Heiskanen et al, 2014;Holgerson, Farr, & Raymond, 2017;Vachon & Prairie, 2013). We calculated the gas fluxes for the 94 lakes that had N 2 O concentrations measured in all four seasons.…”
Section: Calculation Of Gas Fluxesmentioning
confidence: 99%
See 1 more Smart Citation